RIP2 Is a Critical Regulator for NLRs Signaling and MHC Antigen Presentation but Not for MAPK and PI3K/Akt Pathways - Wu, Xiao Man; Chen, Wen Qin; Hu, Yi Wei; Cao, Lu; Nie, Pin; Chang, Ming Xian (Frontiers in Immunology, 2018)
RIP2 is an adaptor protein which is essential for the activation of NF-κB, and NOD1- and NOD2-dependent signaling. Although NOD-RIP2 axis conservatively existed in the teleost, the function of RIP2 was only reported in zebrafish, goldfish and rainbow trout in vitro. Very little is known about the role and mechanisms of piscine NOD-RIP2 axis in vivo. Our previous study showed the protective role of zebrafish NOD1 in larval survival through CD44a-mediated activation of PI3K-Akt signaling. In the present study, we examined whether RIP2 was required for larval survival with or without pathogen infection, and determined the signaling pathways modulated by RIP2. Based on our previous report and the present study, our data demonstrated that NOD1-RIP2 axis was important for larval survival in the early ontogenesis. Similar to NOD1, RIP2 deficiency significantly affected immune system processes. The significantly enriched pathways were mainly involved in immune system, such as “Antigen processing and presentation” and “NOD-like receptor signaling pathway” and so on. Furthermore, both transcriptome analysis and qRT-PCR revealed that RIP2 was a critical regulator for expression of NLRs (NOD-like receptors) and those genes involved in MHC antigen presentation. Different from NOD1, the present study showed that NOD1 but not RIP2 deficiency significantly impaired protein levels of MAPK pathways. Although RIP2 deficiency also significantly impaired the expression of CD44a, the downstream signaling of CD44a-Lck-PI3K-Akt pathway remained unchanged. Collectively, our works highlight the similarity and discrepancy of NOD1 and RIP2 in the regulation of immune signaling pathways in the zebrafish early ontogenesis, and confirm the crucial role of RIP2 in NLRs signaling and MHC antigen presentation but not for MAPK and PI3K/Akt pathways.